Molecular Signalling in Hepatocellular Carcinoma: Role of and Crosstalk among Wnt/β-Catenin, Sonic Hedgehog, Notch and Dickkopf-1 - Alexandros Giakoustidis; Dimitrios Giakoustidis; Satvinder Mudan; Argyrios Sklavos; Roger Williams (Canadian Journal of Gastroenterology and Hepatology)
Hepatocellular carcinoma is the sixth most common cancer worldwide. In the majority of cases, there is evidence of existing chronic liver disease from a variety of causes including viral hepatitis B and C, alcoholic liver disease and nonalcoholic steatohepatitis. Identification of the signalling pathways used by hepatocellular carcinoma cells to proliferate, invade or metastasize is of paramount importance in the discovery and implementation of successfully targeted therapies. Activation of Wnt/β-catenin, Notch and Hedgehog pathways play a critical role in regulating liver cell proliferation during development and in controlling crucial functions of the adult liver in the initiation and progression of human cancers. β-catenin was identified as a protein interacting with the cell adhesion molecule E-cadherin at the cell-cell junction, and has been shown to be one of the most important mediators of the Wnt signalling pathway in tumourigenesis. Investigations into the role of Dikkopf-1 in hepatocellular carcinoma have demonstrated controversial results, with a decreased expression of Dickkopf-1 and soluble frizzled-related protein in various cancers on one hand, and as a possible negative prognostic indicator of hepatocellular carcinoma on the other. In the present review, the authors focus on the Wnt/β-catenin, Notch and Sonic Hedgehog pathways, and their interaction with Dikkopf-1 in hepatocellular carcinoma.